2015
DOI: 10.1007/s13312-015-0628-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels and childhood asthma

Abstract: Blood lead levels are not significantly associated with diagnosis of asthma but elevated blood lead levels seem to be associated with increased asthma severity and higher frequency of eosinophilia and elevated immunoglobulin E levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In agreement with these finding Mohammed et al 2015 found no difference between asthmatic patients and healthy controls in serum lead while serum lead > 10 mg/dl associated with increased severity of asthma and development of eosinophilia and elevated IgE (57) , however they found higher mean values (13.3 , 11.4 µgm/dl ) of lead among patients and controls compared with our study . Previous studies showed that higher blood lead has no relation with development of asthma (57,58) .while other studies (29, 51) showed that higher lead were found in asthmatic patients compared to controls. These last 2 studies despite apparent (61) found that the threshold of blood lead as a risk of asthma development varies among African Americans and Caucasians .…”
Section: Principle Of Test: Copper Forms With-(32dibromo-2-pyridyiazo)mentioning
confidence: 90%
“…In agreement with these finding Mohammed et al 2015 found no difference between asthmatic patients and healthy controls in serum lead while serum lead > 10 mg/dl associated with increased severity of asthma and development of eosinophilia and elevated IgE (57) , however they found higher mean values (13.3 , 11.4 µgm/dl ) of lead among patients and controls compared with our study . Previous studies showed that higher blood lead has no relation with development of asthma (57,58) .while other studies (29, 51) showed that higher lead were found in asthmatic patients compared to controls. These last 2 studies despite apparent (61) found that the threshold of blood lead as a risk of asthma development varies among African Americans and Caucasians .…”
Section: Principle Of Test: Copper Forms With-(32dibromo-2-pyridyiazo)mentioning
confidence: 90%
“…The need for lead testing for young children should be emphasized. Children with asthma with elevated blood lead levels > 10 mcg/dL have higher asthma severity compared to those with lower lead levels (Mohammed, Mohamed, El‐Okda, & Ahmed, 2015). The American Academy of Pediatrics (2016) recommends intervention for any blood level above 5 mcg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that even though blood lead levels are not significantly associated with asthma diagnosis, the elevated blood levels of this metal lead to a more severe form of asthma in children, being related to eosinophilia and elevated immunoglobulin E levels. [ 9 ] The toxicity of blood lead levels on the nervous system is a major concern for children's normal development. According to the data of the Agency for Toxic Substances and Disease Registry (ATSDR), blood lead level in children is associated with encephalopathy.…”
Section: Discussionmentioning
confidence: 99%